Manajemen Wakaf Produktif dan Kontribusinya Terhadap Penguatan Pondasi Ekonomi Masyarakat - Fawait Syaiful Rahman (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2019)
Abstract: the Waqf is one of the productive efforts of an increase in welfare of society as a collective. In a community group, for example, if it turns out that many members of the community who need help, then it can be used productively endowments to help them, for with endowments productive can be obtained access to the funding sources so that generated sufficient capital. The funds obtained through productive endowments can be used as a source of capital so that it can then be used for fertilization of capital on an ongoing basis. On this occasion, the author wished to discuss the development of the following regulasinya, wakaf efforts in improving the economic empowerment of the community through endowments produkti. The methods used in this article is a qualitative approach to the library, where the focus is aimed against any reference about the Waqf and its development. The approach used is qualitative, which is a research procedure that describes the behavior of certain people, events, or places in detail and depth. While this type of research is literature. Namely, research that relies on reading sources, texts, and various information in the form of reading. In a different reference library research is research that is done to solve a problem that is based on a critical study of library materials and related research results presented in new ways.